2017
DOI: 10.1080/13696998.2017.1394866
|View full text |Cite
|
Sign up to set email alerts
|

Real-world comparison of all-cause hospitalizations, hospitalizations due to stroke and major bleeding, and costs for non-valvular atrial fibrillation patients prescribed oral anticoagulants in a US health plan

Abstract: This study demonstrated a significantly higher risk of hospitalization (all-cause, stroke/SE, and major bleeding) associated with warfarin, a significantly higher risk of major bleeding hospitalization associated with dabigatran or rivaroxaban, and a significantly higher risk of all-cause hospitalization associated with rivaroxaban compared to apixaban. Lower major bleeding-related costs were observed for apixaban patients compared to warfarin and rivaroxaban patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 52 publications
(44 reference statements)
3
24
0
Order By: Relevance
“…The remaining 196 studies underwent full-text review, and 25 of those were included in the systematic review. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][34][35][36][37][38][39][40][41]…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The remaining 196 studies underwent full-text review, and 25 of those were included in the systematic review. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][34][35][36][37][38][39][40][41]…”
Section: Search Resultsmentioning
confidence: 99%
“…Five studies used alternative exposure definitions in sensitivity analyses. [20,24,35,37,41] Among the seven studies not explicitly excluding patients with previous VKA use, [11,13,15,35,36,39,41] three accounted for it at the stage of statistical analysis, [11,13,41] while the other four did not. [15,35,36,39]…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies showed that patients initiated on DOACs incur lower healthcare costs than those initiated on warfarin [21][22][23][24] . However, studies that directly compared healthcare costs between patients treated with rivaroxaban and apixaban report mixed results [25][26][27][28] . For example, a retrospective study that included commercially-insured patients who received rivaroxaban or apixaban prior to 2015 found no significant difference in all-cause healthcare costs between patients initiated on apixaban versus rivaroxaban 25 .…”
Section: Introductionmentioning
confidence: 99%